English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

a. 25/16
b. 5/4
c. 25/4
d. 5/2

2007-01-26 10:44:25 · 3 answers · asked by Anonymous in Science & Mathematics Mathematics

3 answers

The answer is part c.: 25/4. Here's why:

(x + b)^2 = x^2 + 2 b x + b^2. Clearly, from the term in x, b = 5/2. Therefore:

c = b^2 = (5/2)^2 = 25/4. QED

Live long and prosper.

2007-01-26 10:53:57 · answer #1 · answered by Dr Spock 6 · 0 0

We want to find c so that x^2 + 5x + c can be written as (x + m)^2 for some number "m". If we multiply (x+m)^2 out, we get x^2 = 2mx + m^2. So to get this to match the original trinomial, we need 5 = 2m and c = m^2. This means m = 5/2, c must equal (5/2)^2 or 25/4. So the correct answer is "c".

2007-01-26 18:57:41 · answer #2 · answered by Anonymous · 0 0

To get a perfect square trinomial in that form,
you need 5 = 2(sqrt c)

so:

5 = 2(sqrt c)
5/2 = sqrt c
25/4 = c

2007-01-26 18:53:57 · answer #3 · answered by Mathematica 7 · 0 0

fedest.com, questions and answers